Effects of different sowing dates on biomass allocation of various organs and allometric growth of Fagopyrum esculentum - Wang, Heqi; Wang, Congwen; Fan, Gaohua; Fu, Changxing; Huang, Yingxin; Liu, Xuhe; Wang, Shirui; Wang, Kunling (Frontiers in Plant Science, 2024)
The sowing date has an important influence on the growth and reproduction of plants, yet its specific effect on biomass allocation and allometric growth remains unclear. In this study, we conducted a field experiment involving the sequential sowing of Fagopyrum esculentum from April 12th to August 11th in 2018. Subsequently, we measured biomass across various plant organs and calculated the corresponding biomass allocation. Furthermore, we conducted a detailed analysis of the allometric growth relationship concerning the varied organ biomass. We found that the organ biomass accumulation and allocation of buckwheat were significantly affected by the sowing dates. Delayed planting time not only resulted in diminished vegetative growth but also prompted an increased allocation of biomass toward reproduction in buckwheat. Moreover, delayed planting had significant effects on the allometric exponent, constant, and individual size of the buckwheat. Interestingly, the allometric exponents (both dynamic and static) governing the relationship between reproductive vs. vegetative biomass and belowground vs. aboveground biomass exhibited a contrasting tendency from the early to late sowing dates. However, the effects of sowing dates on biomass of F. esculentum varied with different stages of growth. Particularly for those sown late, the maximum reproductive biomass significantly exceeded that of plants sown on the early and middle dates. In summary, our results contribute to a nuanced understanding of the plant size-reproductive biomass relationship under different sowing dates and underscore the pivotal role of planting time in shaping mature plant sizes and reproductive biomass.